Built on Values : Creating an Enviable Culture that Outperforms the Competition. - Rhoades, Ann (John Wiley & Sons, 2011)
Most leaders know that a winning, engaged culture is the key to attracting top talent--and customers. Yet, it remains elusive how exactly to create this ideal workplace --one where everyone from the front lines to the board room knows the company's values and feels comfortable and empowered to act on them. Based on Ann Rhoades' years of experience with JetBlue, Southwest, and other companies known for their trailblazing corporate cultures, Built on Values reveals exactly how leaders can create winning environments that allow their employees and their companies to thrive. Companies that create or.